PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PELECEHAN SECARA VERBAL DI LINGKUNGAN KERJA MELALUI WHATSAPP - Sari, Nur Eka (Lex LATA, 2024)
Public awareness and law enforcement in handling sexual harassment cases so far are still lacking to be able to provide a deterrent effect because these cases still occur frequently, especially cases of verbal sexual harassment that often occur through social media.  The crime of sexual harassment in the work environment through social media can be categorized as cyberharassment, but the article used to ensnare the perpetrator is not a pure article but an article that discusses crimes of decency because there is no specific regulation governing this matter so that victims of verbal sexual harassment through social media are not easy to report the case due to limited evidence and constraints from the legislation itself. With the unclear regulations that specifically regulate verbal harassment and violence, this will continue to cause violations of human rights against decency, so that legal protection is needed for victims of verbal harassment in the work environment through Whatsapp social media.